Deformability Behavior of St3 Steel Used in the Profiles of High-Voltage Poles - Jutas, A.; Mockiene, J.; Vaiciukynas, V.; Zaldarys, G.; Cinelis, G. (Проблемы прочности, 2018)
The reasons for the difference in mechanical properties of cold-rolled angles made of low-carbon St3 steel used in old designs of high-voltage poles are established. Several kinetic curves for mechanical properties were investigated in terms of tangential and plastic moduli as the most appropriate tool since the integrating parameters can present some strength and deformability differences much more clear at any stage of deformation. The original quantitative characteristics were presented to eliminate the manufacturing quality effect of pole elements and demonstrate the importance of deformation behavior in explaining the microstructural variety. The microstructural phenomena may affect stress levels at the points of yielding, ultimate strength, and fracture.